2020
DOI: 10.3390/info11070367
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits, Gamification and Features to Develop an App to Reduce Physical Inactivity

Abstract: Background: Health benefits from physical activity (PA) can be achieved by following the WHO recommendation for PA. To increase PA in inactive individuals, digital interventions can provide cost-effective and low-threshold access. Moreover, gamification elements can raise the motivation for PA. This study analyzed which factors (personality traits, app features, gamification) are relevant to increasing PA within this target group. Methods: N = 808 inactive participants (f = 480; m = 321; age = 48 ± 6) were int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The PAHCO model with its multidimensional and integrative view has recently been used in different target groups and settings attributable to both prevention (12,(14)(15)(16)(17)(18)(19) and rehabilitation (12,(20)(21)(22)(23). However, when reviewing the first conceptualtheoretical articles, it becomes obvious that environmental factors hardly play any role within this competence approach (11,24).…”
Section: Figure 1 |mentioning
confidence: 99%
“…The PAHCO model with its multidimensional and integrative view has recently been used in different target groups and settings attributable to both prevention (12,(14)(15)(16)(17)(18)(19) and rehabilitation (12,(20)(21)(22)(23). However, when reviewing the first conceptualtheoretical articles, it becomes obvious that environmental factors hardly play any role within this competence approach (11,24).…”
Section: Figure 1 |mentioning
confidence: 99%
“…Furthermore, they concluded that the problem of inactive participants should, in fact, be addressed with app features and gamification elements in accordance with their prior defined goals rather than with their personality traits. Nevertheless, with respect to earlier studies suggesting personality traits being associated with higher stress vulnerability and potentially different stress management competencies, we hypothesize that the results by Meixner et al [ 65 ] might not be transferable to stress outcomes and tailored app features.…”
Section: Introductionmentioning
confidence: 60%
“…The personality questions were derived from previous qualitative interviews and checked for construct validity using the Visual Questionnaire [ 65 ]. The personality analysis included health-specific questions, which resulted in a manifestation of 4 personality dimensions (need for security, information acquisition, need for stimulation, and information processing).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different variations of gamification capabilities have also been examined in the context of employees' online self-disclosure (Dincelli and Chengalur-Smith, 2020) and corruption behaviors (Baxter et al, 2017). In addition, previous work on gamified systems have relied on both monetary and non-monetary rewards to incentivize participants (Lewis et al, 2016;Karac and Stabauer, 2017;Meixner et al, 2020;Ueyama et al, 2014). It is evident that gamification can be a useful tool in educating and motivating individuals in a variety of contexts.…”
Section: Background On Phishingmentioning
confidence: 99%